Justice and security in the 21st century : risks, rights and the rule of Law - Ugelvik, Synnve, 1978-; Hudson, Barbara, 1945- (Abingdon, Oxon : Routledge, 2012)
'This book examines the question of whether justice or security is the primary virtue of 21st-century society. The problem of enhancing security without undermining justice managing risk without undermining the rule of law has always confronted society. However, recent developments such as new counter-terrorism measures, the expanding scope of criminal law, harsher migration control and an increasingly pronounced concern with public safety, have posed new challenges. According to the authors of this volume, the key element of these contemporary challenges is that of membership and exclusion: that is, who is to be included within the community of justice, and against whom is the just community aiming to defend itself? This book brings together researchers from various academic disciplines and different countries in order to explore these developments. It attempts to chart the complex landscapes of justice, human rights and the rule of law in an era when such ideals are challenged by increasing demands for efficiency, effectiveness, public safety and security. The book comprises four parts, based on their relation to different aspects of these new landscapes of justice and security: Situating the subjects of security, criminalization, control and security; The new balancing of justice and security; Changing structures and concepts of legitimacy.This book will be of much interest to students of critical legal studies, criminology, critical security studies, human rights, sociology and IR in general'--
Who needs justice? who needs security? -- EU citizenship and the new landscape of fundamental rights : a conceptual sea change -- The justice of crimmigration law and the security of home -- Imprisoned on the border : subjects and objects of the state in two Norwegian prisons -- Punishing the uncommitted crime : prevention, pre-emption, precaution and the transformation of criminal law -- Iit takes a crisis : dilemmas of democracy in Norwegian emergency law -- Urbanscapes of injustice and insecurity -- Security, justice and the criminal justice system : remarks on EU criminal law -- Constitutional exceptionalism : efficacy, proportionality and the attenuation of balancing standards -- Policing the law of fear? -- Security versus justice : the individualisation of security and the erosion of citizenship and fundamental rights -- States of security : how the Lisbon treaty changes areas of freedom, security and justice.
Includes bibliographical references and index.
Includes bibliographical references and index.
Keywords: Criminal justice, Administration of -- Europe; War and emergency legislation -- Europe; National security -- Law and legislation -- Europe; Terrorism -- Prevention -- Law and legislation -- Europe; Civil rights -- Europe